Orange Juice and Its Component, Hesperidin, Decrease the Expression of Multidrug Resistance-Associated Protein 2 in Rat Small Intestine and Liver - Watanabe, Minoru (Hindawi Publishing Corporation, 2011)
We investigated the effects of orange juice (OJ) or hesperidin, a component of OJ, on the pharmacokinetics of pravastatin (PRV) and the expression of both protein and mRNA of multidrug resistance-associated protein 2 (Mrp2) in the rat small intestine and liver. Eight-week-old male Sprague-Dawley rats were used in this study. OJ or a 0.079% hesperidin suspension was administered orally for 2 days. Tap water was given as a control. A single dose of PRV at 100 mg/kg p.o. was administered after 2 days of OJ, hesperidin, or tap water ingestion. The AUC, C(max), and t(1/2) values of PRV were significantly increased in OJ group. Mrp2 protein and mRNA levels in the small intestine and liver, respectively, were significantly decreased after the ingestion of OJ. The same results were obtained with hesperidin. These results suggest that the changes in PRV pharmacokinetic parameters and the decrease in Mrp2 expression caused by OJ are due to hesperidin in the juice.